2018
DOI: 10.1186/s12864-018-4668-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of the honeybee parasite Varroa destructor provides new biological insights into the mite adult life cycle

Abstract: BackgroundThe parasite Varroa destructor represents a significant threat to honeybee colonies. Indeed, development of Varroa infestation within colonies, if left untreated, often leads to the death of the colony. Although its impact on bees has been extensively studied, less is known about its biology and the functional processes governing its adult life cycle and adaptation to its host. We therefore developed a full life cycle transcriptomic catalogue in adult Varroa females and included pairwise comparisons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 97 publications
2
29
0
Order By: Relevance
“…Detection mainly included the genomic positive strand DWV RNA (Supplementary Data Table S1). RT-qPCR was carried out essentially as previously described 28,39 , DWV RNA copy numbers were log-transformed prior to statistical analyses. Negative-strand DWV RNA quantification was carried using two sets of primers designed for targeting different regions in the DWV genome, Assay 1 (region 4909-5008 nt) 16 and Assay 2 (region 7303-7503 nt) 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Detection mainly included the genomic positive strand DWV RNA (Supplementary Data Table S1). RT-qPCR was carried out essentially as previously described 28,39 , DWV RNA copy numbers were log-transformed prior to statistical analyses. Negative-strand DWV RNA quantification was carried using two sets of primers designed for targeting different regions in the DWV genome, Assay 1 (region 4909-5008 nt) 16 and Assay 2 (region 7303-7503 nt) 40 .…”
Section: Methodsmentioning
confidence: 99%
“…As well as being involved in the initiation of pupation in honey bees, ecdysone and its derivatives also act as a trigger for vitellogenesis in the Acari (Cabrera et al, ; Mondet et al, ; Roe, Donohue, Khalil, & Sonenshine, ). Like many specialized parasites, Varroa exhibits reduced metabolic pathways even when compared to other parasitic Acari and Arthropods (Cabrera et al, ; Grbić et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Varroa genome is estimated as 565 Mbp, but consists of short and mostly unannotated sequences (Cornman et al, 2010;Campbell et al, 2015). Recently, transcriptomic and proteomic analysis by us and others showed differential expression in the different developmental stages of the adult mite, emphasizing the profound modifications taking place thorough the mite's life cycle (Eliash et al, 2017;Mondet et al, 2018). The aim of the present research focuses on the Varroa chemosensory machinery by comparing transcriptomic and proteomic profiles between the forelegs (at different physiological stages) and the rear legs.…”
Section: Introductionmentioning
confidence: 98%
“…However, very little is known regarding chemosensing in non-insect arthropods such as ticks and mites, despite their economic and agricultural significance. Nonetheless, in recent years, data on Chelicerata have begun to accumulate, mostly from genomic, transcriptomic and proteomic studies (Gulia-Nuss et al, 2016;Hoy et al, 2016;Iovinella et al, 2016;Vizueta et al, 2016;Eliash et al, 2017;Mcafee et al, 2017;Renthal et al, 2017;Mondet et al, 2018). These studies have revealed potential homologues of some of the known insect chemosensory protein families, based on sequence similarities.…”
Section: Introductionmentioning
confidence: 99%